Features of application of punishments minor (Journal of actual problems of jurisprudence, 2019)
Effective application of punishment under the criminal code of RK is important in fight against crime among minors.The author also in article brings up questions of creation and of theoretical development of uniform science of youthstudies and new institute – coercive measures of correctional influence.Key words: crime prevention, crime among minors, youth studies, illegal behavior, legal deviation, coercive measuresof medical character, coercive measures of educational influence, coercive measures of correctional influence.